Vertical migration timing illuminates the importance of visual and nonvisual predation pressure in the mesopelagic zone. Issue 8 (9th June 2021) - Benoit‐Bird, Kelly J.; Moline, Mark A.
Abstract: Each day, motile pelagic organisms of all sizes undergo vertical movements tied to sunset and sunrise. Diel migration of animals is thought to result from the competing need to feed in energy rich surface waters while avoiding visual predators. Previous study using a newly adapted autonomous vehicle to measure individual characteristics in scattering layers provided the first measures of the internal layer structure, demonstrating that deep scattering layers can be made up of many topologically scaled, mono‐specific aggregations, or "schools." Follow‐up measurements presented here show these schools of mesopelagic animals remain coherent during upward migration at dusk. We found that groups of smaller animals began migrating sooner each night than larger individuals, consistent with their relatively lower detectability by visual predators. We also found a correlation with taxonomic differences in swimming capabilities, suggesting that the ability to avoid predators if they are encountered also plays a role in the patterns of migration observed. The presence of acoustic predators, Risso's dolphins ( Grampus griseus ), however, altered this pattern for their primary prey, causing squid to remain at depth for approximately 40 min longer than others. The risk of predation by this air‐breathing predator decreases with depth, making delaying migration an appropriate response to this largely nonvisual predation risk. Understanding the timing of individual migration patterns provides insights into the bioenergetic and predator–prey processes in the mesopelagic zone that are critical for understanding the ecological and biogeochemical impacts of these high biomass layers in the ocean.